Samsung vs. Apple: How different communication strategies affect consumers in Portugal - Margarida Almeida; Eva Sousa; Carolina Rodrigues; Maria Beatriz Candeias; Manuel Au-Yong-Oliveira (Administrative Sciences, 2021)
It is indisputable that technology is present in everyday life. In this digital era, brands need to adapt to the changing pace of the needs and desires of society to distinguish themselves from their adversaries, especially in the electronic environment. Hence, they must have well-defined and successful marketing and advertising strategies to achieve a place on the podium of preference of consumers. This work intends to understand how the communication strategies of Apple and Samsung affect the decisions of consumers in Portugal to buy electronic devices. To this end, a survey was conducted, and the responses of 700 individuals who reside in Portugal were analysed through descriptive and inferential (chi-square test of independence) statistics. The survey results show that cost-benefit, price, technical specifications, and performance are the characteristics that weigh the most when purchasing electronic devices, as well as the perceived prestige of the brand. Additionally, an association was found between having only one device and having more products of the brand, with Apple users having more frequently more than one of the brand's products than Samsung users. We thus concluded that Apple consumers are more loyal. It was also found that the store where the devices are brought is not independent, in Portugal, of the brand of the devices. Apple users buy more brand products from the brand store, both physical and online, than Samsung users. Finally, advertisements and word-of-mouth were found to be fundamental for consumers to acknowledge brand devices, and the degree in which this happens is also not independent of the brand, in Portugal, as a chi-square independence test showed.
Keywords: 350; advertisement; Apple; marketing strategy; Samsung; social media